The Effects of Sme's Access to Finance on non-Bank Financial Institutional Loans - Sisca Contesa (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
This study aims to investigate the effect of access to finance on non-bank financial institutional (NBFI) loans. The tenet is that SMEs with less access to finance will pursue loans provided by the NBFI despite its higher interest rates. Using World Bank Enterprise Survey data, the findings show the positive relationship between SMEs' access to finance and NBFI loans. It affirms our hypothesis and aligns with Pecking Order Theory. This research contributes to the literature by revealing NBFI loans as alternative financing for SMEs due to their severe access to finance. Practically, the policymakers should consider giving more incentives on NBFI loans; hence, Indonesian SMEs have more room to finance their operation.